Islam Moderat dan Problem Isu Keislaman Kontemporer di Masjid Nasional Al-Akbar Surabaya - Muktafi Muktafi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2016)
This article attempts to examine mainstreaming of the Moderate Islam together with the problem of contemporary Islamic issues at Al-Akbar National Mosque Surabaya. The article observes a number of issues such as liberalism, radicalism, and pluralism in the view of the Muslim preachers (d?‘i) of Al-Akbar National Mosque. The mainstreaming of the Moderate Islam has been a manifestation of recognition and reverence of the mosque management, especially the preachers in regard with a number of different religious entities in Islam. Responding to the issues, the preachers assert that the Moderate Islam contains not merely conformity with the context of socio-cultural aspect, but also the manifestation of “Islamness” which is compatible with understanding of Ahl al-Sunnah wa al-Jam?‘ah. What is meant here by the Islamness is a characteristic of religiosity, which puts emphasis on three aspects, namely al-taw?su?, i‘tid?l, and taw?zun. Commonly, the cultivation of moderatism values at Al-Akbar National Mosque rests on the process of teaching, study, and da‘wa (preaching) activities. These activities have been implemented in persuasively subtle manner focusing on peaceful religious messages. The preachers argue that although moderatism has been usually seen as acceptance toward heterogeneity, it does not refer to any acknowledgement of such heterogeneity as a part of truth in one’s belief.